Protocol of the MOVI-ageing randomized controlled trial: a home-based e-Health intervention of cognitively demanding exercise for the improvement of cardiorespiratory fitness and cognitive function in older individuals - Alvarez-Bueno, Celia; Lucerón-Lucas-Torres, Maribel; Ruiz-Hermosa, Abel; Sequí-Dominguez, Irene; Venegas-Sanabria, Luis Carlos; Medrano-Echeverria, Maria; Visier-Alfonso, María Eugenia; Rodriguez-Martin, Beatriz (Frontiers in Public Health, 2023)
Objective: To describe the protocol of the MOVI-ageing randomized controlled trial, a home-based eHealth intervention of cognitive-demanding exercise for older adults, in improving global cognitive function and basic cognitive functions, cardiorespiratory fitness, and muscle fitness. Methods: This randomized controlled trial will include participants identified in the social centres of Cuenca and Talavera de la Reina who agree to participate and provide informed consent. Adults aged 60-80 years of both genders retired regardless of the reason for retirement, who do not meet frailty criteria according to Fried criteria, and without cognitive impairment will be invited to participate. This study will be developed in two phases: i) a 12-week randomized efficacy/feasibility trial and ii) a large-scale implementation randomized trial phase with a 12-week follow-up following similar procedures. In addition, a qualitative study on barriers to and facilitators of the implementation of the physical exercise intervention using eHealth for older people will be conducted. Participants will have access to a platform including videos of cognitively demanding physical exercise. The participants will be remotely and off-line guided through the physical exercise intervention, and the research team will be able to check the degree of compliance with the program and its correct execution. The participants will receive feedback on their compliance with the routines and reinforcement messages. Implications: The implementations of the findings and their inclusion in guidelines may directly impact in older people’s life, and relatives, through the prevention of morbidity and the reduction of years lost to disability. These benefits may be reflected in the reduction of economic expenditure by reducing the demand for social and health care services. Ethics: The Clinical Research Ethics Committee of the ‘Virgen de la Luz’ Hospital in Cuenca approved the study protocol (registration number: 2022/PI3222). In addition, this protocol was previously registered in Clinical trials.gov. (Number: NCT05928078).